Rootedness. Civilization and Barbarism in Simone Weil - Herrando Cugota, Carmen (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
We are currently undergoing a Civilization crisis similiar to the one that took place in Europe during the interwar period on the first half of the XX century. The French philosopher Simone Weil (1909-1943) figured and adressed this issue on several texts, offering some clues on how to build a new Civilzation from her own social, political and religious experience. It is particularly relevant her last and unfinished book: L’Enraciment, branded by Albert Camus as a real «Treaty of Civilization». But her reflection about this issue extends throughout her entire work, an example o authentic intelectual probity.
Keywords: civilization; rootedness; mystic; politics; force; work